Infrastructure and Structural Change in the Horn of Africa - Herrera Dappe, Matias; Lebrand, Mathilde (World Bank, Washington, DC, 2021)
Access to infrastructure supports economic development through both capital accumulation and structural transformation. This paper investigates the links between investments in electricity, Internet, and road infrastructure, in isolation and bundled, and economic development in the Horn of Africa, a region that includes countries with different levels of infrastructure and economic development. Using data on the expansion of the road, electricity, and Internet networks over the past two decades, it provides reduced-form estimates of the impacts of infrastructure investments on the sectoral composition of employment. Bundled infrastructure investments cause different patterns of structural transformation than isolated infrastructure investments. The impact of bundled road and electricity investments on reducing the sectoral employment share in agriculture is found to be 2.5 times larger than the impact of roads alone. The paper then uses a spatial general equilibrium model to quantify the impacts of future regional transport investments, bundled with electricity and trade facilitation measures, on economic development in countries in the Horn of Africa.